Dancing Into Ubuntu: Inquiring Into Pre-Service Teachers' Experiences of Kpanlogo, A West African Dance - Pingue, Kahmaria (Université d'Ottawa / University of Ottawa, 2018)
This thesis questions what it was like for pre-service teachers registered in a Bachelor of Education program to experience Kpanlogo, a West African dance from Ghana. Over a period of two years, the primary researcher introduced this dance to her peers first as a pre-service teacher, and then as a graduate student in a variety of ways: 1) practicing it for a performance at a community building talent show on campus, 2) learning it through a professional development workshop, and 3) teaching it to intermediate students at a local school, on two different occasions. Five pre-service teachers responded to an invitation to participate in a phenomenological study about their experiences. The two research questions which guided the interviews were: 1) What was it like to experience Kpanlogo, a West African dance, as a pre-service teacher? 2) What was it like as a pre-service teacher to teach students Kpanlogo? The conceptual framework of Sankofa Cyclical Waves, situated in a collectivist African Worldview orients us to the philosophy of Ubuntu, which posits that humanness is found and cultivated within community. Sankofa, a Ghanaian proverb which encourages its people to go back, physically or spiritually, to retrieve what was once lost or forgotten was used as a particular path to analyze the lived experiences of the pre-service teachers. In this thesis the Sankofa Cyclical Waves provided a structure to identify their various levels of understanding Ubuntu. Experiences analyzed as being novice in nature were awkward at the start, then as the dancer moves towards the end of the continuum, towards Ubuntu, the dancer moves through a series of waves as they become more familiar with rhythms, movements, African dance attire, and becoming a part of the whole; the Other‘s community.
Keywords: African dance; Ubuntu; Kpanlogo; Sankofa; Pre-Service; Teachers; Culturally Relevant Curriculum; Culture; Phenomenology; Education; Dance; African Indigenous Knowledge; African Worldview; Community